2014
DOI: 10.1080/14786419.2014.989391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epigallocatechin gallate on the cell-wall structure ofMycobacterial smegmatismc2155

Abstract: Epigallocatechin gallate (EGCG) is the main component of green tea extracts that inhibits the growth of Mycobacterial smegmatis mc(2)155, and the mechanism is not clear. This study showed the effects of EGCG on the growth of mc(2)155. The content and the structure of EGCG in LB medium with mc(2)155 were identified by HPLC and LC/MS. Transmission electron microscopy was utilised to identify the cell envelope structure. As a result, the optional inhibition concentration was determined to be 20 μg mL(-1). Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…EGCG, the most abundant catechin present in green tea, has been shown to have anti-mycobacterial effects by inhibiting Mtb enoyl-acyl reductase (InhA), an enzyme involved in the production of functional mycolic acids [16]. Structural damage in the mycobacterial cell wall due to impaired production of mycolic acids has been postulated as a mechanism behind the anti-mycobacterial function of EGCG [15]. In experimental studies, mice infected with Mtb had significantly increased levels of oxidative stress during early stages of tuberculosis, and oral administration of green tea extract led to the reversion of oxidative stress parameters to near normal levels [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG, the most abundant catechin present in green tea, has been shown to have anti-mycobacterial effects by inhibiting Mtb enoyl-acyl reductase (InhA), an enzyme involved in the production of functional mycolic acids [16]. Structural damage in the mycobacterial cell wall due to impaired production of mycolic acids has been postulated as a mechanism behind the anti-mycobacterial function of EGCG [15]. In experimental studies, mice infected with Mtb had significantly increased levels of oxidative stress during early stages of tuberculosis, and oral administration of green tea extract led to the reversion of oxidative stress parameters to near normal levels [13].…”
Section: Discussionmentioning
confidence: 99%
“…Green tea extract has been reported to reduce oxidative stress associated with tuberculosis in infected mice in an experimental study [13], and in tuberculosis patients in a clinical study [14]. Epigallocatechin gallate (EGCG), the major component of green tea catechins, has also been shown experimentally to inhibit mycobacterial survival [15,16,17]. Epidemiological evidence to support the role of tea drinking in the development of tuberculosis is scarce; only one recent case-control study has reported tea drinking to be inversely associated with prevalent tuberculosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…The cell membrane of MTB contains broad diversity of lipid molecules that are responsible for pathogenesis [25][26][27]. The disruption of membrane integrity in presence of Van as reported previously and role of lipids in development of MDR prompted us further to elucidate its mechanism and involvement of lipid associated changes in the present study [10,28].…”
Section: Discussionmentioning
confidence: 99%
“…A second study examined tea polyphenols that target the mycobacterial cell wall [100]. Mycobacterium smegmatis mc2 155 was incubated in Luria-Bertani (LB) broth and subjected to various concentrations of EGCG derived from green tea.…”
Section: Tea Polyphenolsmentioning
confidence: 99%
“…Suspended mycobacterial cells were later subjected to electron microscopy, liquid chromatography-mass spectrometry (LC-MS) and high-performance liquid chromatography (HPLC)). Electron microscopy indicated structural damage to the Mycobacterium cell wall with increasing amounts of EGCG; authors indicated that the optimal concentration of EGCG causing bacterial cell wall damage was 20 µg/mL [100]. The content and structure of EGCG in LB media was confirmed by HPLC and LC-MS; both procedures are utilized in laboratories to isolate the individual components of a mixture [100].…”
Section: Tea Polyphenolsmentioning
confidence: 99%